PENGARUH PENDAPATAN ASLI DAERAH (PAD) DAN DANA PERIMBANGAN TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH - Padang, Novi Natalia (LPPM Universitas Katolik Santo Thomas Medan, 2023)
The purpose of this study was to determine and analyze the effect of regional own-source revenue (PAD) and balancing funds partially on the financial performance of local governments in the districts/cities of North Sumatra Province. The population for this study is the districts/cities of North Sumatra Province, consisting of 33 districts/cities with the observation years 2014 to 2021. The type of sample uses a saturated sample where the population is the sample. The data is processed using the panel data regression statistical test method. The results of this study prove that regional own-source revenue, balancing funds partially have a positive and significant effect on the financial performance of local governments in the districts/cities of North Sumatra Province.